RESEARCH ON THE OPTIMAL SYNTHESIS OF A MULTI-CONTOUR MECHANISM - Dorin Bădoiu (Romanian Journal of Petroleum & Gas Technology)
The synthesis of mechanisms is a complex field of study that includes, in addition to the knowledge necessary for the correct configuration of working mechanisms and those necessary for their analysis, knowledge from the field of nonlinear programming that involves the calculation of the extrema of an objective function, possibly subject to some constraints. In this context, the dimensional synthesis of the mechanisms that involves the establishment of an optimal set of dimensions of the component elements to ensure the necessary precision of the operating parameters remains an always current field through its multiple applications. The paper presents a method of dimensional synthesis of a multi-contour mechanism for which certain values of the stroke of a component piston and the positions of the driving element of the mechanism in which the change of the direction of movement of the piston takes place are imposed. Through the dimensional synthesis of the analyzed mechanism, it is aimed that, in addition to the mentioned conditions, a minimum value of the sum of the lengths of the component elements is obtained. To achieve the optimal synthesis, the Sequential Quadratic Programming (SQP) method included in the Optimization package from the Maple program was used.